Book review: “Worlds of Japanese Culture” by Elena L. Skvortsova and Alexander L. Lutsky - S. A. Polkhov (Японские исследования)
The article examines the contents of the book “Worlds of Japanese Culture” by E.L. Skvortsova and A.L. Lutsky (Moscow, St. Petersburg: Center for Humanitarian Initiatives, 2025. 582 p. Series “Tree of Meanings.” ISBN 978-5-98712-499-4). The review outlines the main topics addressed by the authors of the book: the development of Japanese philosophy and sociology in the modern period, the problems faced by Japanese society in the 21st century, the essence and characteristic features of Japanese civilization. According to the author of the review, the book is a valuable contribution to the study of modern philosophy and culture of Japan as a whole.